Effect of mixed fillers on positive temperature coefficient of conductive polymer composites. Issue 2 (2nd April 2016) - Asare, Eric; Basir, Al; Tu, Wei; Porwal, Harshit; Zhang, Han; Liu, Yi; Evans, Jamie; Newton, Mark; Peijs, Ton; Bilotti, Emiliano
Abstract: This paper investigates the trade-off between low percolation threshold and large positive temperature coefficient (PTC) intensity in conductive polymer composites (CPCs). Conductive particles with low aspect ratios and large dimensions have been demonstrated to induce large PTC intensity in CPCs. Conversely high aspect ratio conductive (nano)particles like carbon nanotubes (CNTs) are desirable because of their extremely low percolation threshold (typically well below 1 wt.%), providing benefits in terms of reduced density, brittleness, costs and improved processability. Herein we report on combinations of different conductive fillers to explore the possibility to obtain both low percolation threshold and high PTC intensity. For the first time we use model systems in which at least one of the two conductive fillers is of relatively homogenous size and shape to facilitate unraveling some of the complicated inter-relationships between (mixed) conductive fillers and the PTC effect. Graphical abstract: